Development Of Virtual Reality Gis For Cultural Heritage Conservation (Case Study: Sewu Temple) - Ririn Threesiana; Deni Suwardhi; Sugeng Riyanto (Indonesian Journal of Geospatial, 2013)
Abstract. Cultural heritage is an asset owned by any country that can tell behavior of people's life there. The story of the cultural heritage